Challenges in Diagnosing Muckle‐Wells Syndrome: Identifying Two Distinct Phenotypes. Issue 5 (May 2014) - Kuemmerle‐Deschner, Jasmin B.; Dembi Samba, Samuel; Tyrrell, Pascal N.; Koné‐Paut, Isabelle; Marie, Isabelle; Deschner, Norbert; Benseler, Susanne M.
<x xml:space="preserve">Abstract</x> Objective The diagnosis of Muckle‐Wells syndrome (MWS) remains challenging due to the clinical heterogeneity and lack of diagnostic criteria. The aims of this study were to describe key elements of the diagnostic evaluation process in MWS and compare identified variables between patients diagnosed in childhood and adulthood. Methods A cohort study of consecutive patients with a clinical and genetic diagnosis of MWS was conducted at 2 reference centers for autoinflammatory diseases. Demographic information, clinical presentation, access to care, and preclinical evaluation variables were captured. Presenting symptoms were compared between groups of patients diagnosed in childhood and adulthood. Prediction analysis explored variables associated with late diagnosis. Correspondence analysis identified clinical phenotypes. Results A total of 34 MWS patients were included (16 males, 18 females) and median age at diagnosis was 31.5 years (range 0.5–75 years). Patients diagnosed during childhood reported musculoskeletal symptoms (62%), rash (62%), fever (54%), and abdominal pain (31%). Those diagnosed as adults described musculoskeletal symptoms (86%), rash (67%), hearing loss (52%), and fatigue (29%). Hearing loss was associated with late diagnosis, while access‐to‐care variables were not predictive. Correspondence analysis identified distinct clinical phenotypes as follows: an "inflammatory phenotype" (most commonly seen in patients diagnosed in childhood and characterized by relapsing fever and abdominal pain), an intermediate phenotype, and an "organ‐disease" phenotype in patients diagnosed during adulthood and characterized by fatigue and hearing loss. Conclusion Distinct clinical phenotypes were identified in patients with MWS. These are closely related to age at diagnosis. The presence of these phenotypes has to be considered when developing diagnostic criteria for MWS.